Analisis Pengaruh Bahan Ajar Kimia Berbasis IT Terhadap Keterampilan Kolaborasi dan Komunikasi Siswa - Aldian, Hendy; Wahyudiati, Dwi (Jurnal Paedagogy, 2023)
This study aims to analyze the impact of IT-based teaching materials on students' collaboration and communication skills when working with chemical bonding materials. It was a quantitative experimental study that used the problem-based learning (PBL) model. Field trials were performed in the experimental class (class X A) and the control class (class X B). These samples were determined through Saturated Sampling and Quasi-experiments design pretest, posttest, and Non-Equivalent Control Group design. Furthermore, the data were collected from the student communication and collaboration observation research sheet and were analyzed using an ANOVA test. The results showed that students' communication and collaboration skills in the experimental class increased, with an average score of 40 to 71.75 for student communication and 89.97 for student collaboration. As for the control class, the average score was from 41 to 45.67 for student communication, and the average score was 63.33 for student collaboration. The results of this study can be used as input for teachers and pre-service teachers to choose appropriate teaching materials to train students' communication and collaboration skills.